The use of calixarene as ionophores in potentiometric ion-selective electrodes of naftidrofuryl oxalate using microsized membrane sensors for kinetic study of naftidrofuryl (NFT) degradation - El-Sayed, Mohammad Abdalla (European Journal of Chemistry, 2013)
Novel miniaturized polyvinyl chloride membrane sensors in all-solid state graphite and platinum wire supports were developed, electrochemically evaluated and used for the assay of naftidrofuryl oxalate. The naftidrofuryl oxalate sensors were based on the formation of an ion-association complex between the drug cation and tetrakis-(4-chlorophenyl)borateanionic exchanger as electroactive material and sulfocalix-8-arene as ionophore dispersed in a polyvinyl chloride matrix. Linear responses of 10-2-10-6 M and 10-2-10-5 M with cationic slopes of 56.9 mV and 54.1 mV over the pH range 2-5 were obtained by using the naftidrofuryl oxalate-coated graphite (Sensor 1) and platinum wire (Sensor 2) membrane sensors, respectively. The utility of 4-sulfocalix-8-arene as ionophore had a significant influence on increasing the membrane sensitivity and selectivity. The methods were also used to determine the intact drug in the presence of it’s degradate in Praxilene® tablets, plasma and cerebrospinal fluid with good recovery. Sensor 1 was used to study the kinetics of naftidrofuryl oxalate alkaline degradation that was found to follow a pseudo first-order reaction. The activation energy could be estimated from the Arrhenius plot to be 12.572 Kcal/mol.